Measurement of Capability Level Using COBIT 5 Framework (Case Study: PT Andalan Bunda Bijak) - Dicky Sanjaya; Melissa Indah Fianty (Universitas Multimedia Nusantara, 2022)
PT Andalan Bunda Bijak is a company engaged in the distribution of baby equipment. In running its business, PT Andalan Bunda Bijak implements a system called MySoft to assist the company's business activities. The business development of the company has not fully run optimally. This is because there are still problems related to risk management (no SOP for handling problems, no division to handle problems, and no problem recording) and information security (no information security policy and no information security training). With this problem, it is necessary to measure the level of capability in corporate information technology governance. This study was conducted to analyze the level of corporate information technology governance capability using the COBIT 5 framework. This study uses 3 domains (EDM, APO, and DSS) and 4 processes (EDM03, APO12, APO13, and DSS05) obtained from the mapping results of PT Andalan Bunda Bijak's vision, mission, goals, and strategies for the problems faced by the company. Data was collected by interviewing the company's operational leaders and managers and observing the systems, documents, and company environment. The results of this study determined that each process was at level 1 (performed process). There is a gap of 1 level between the level of capability of the company's current state and the level of capability of the company's expectations. There are 28 recommendations for improvement given to the company.